Eletrocardiograma em cães: revisão - Martinello, Luciene Maria; Romão, Felipe Gazza; Dan De Nardo, Carla Daniela; Machado, Luiz Henrique de Araújo; Lourenço, Maria Lucia Gomes [UNESP]; Fernadez Vailati, Maria do Carmo (My University, 2011)
The electrocardiogram (ECG) is an important tool used in the diagnosis of cardiac arrhythmias, since it gives the graphic representation of depolarization and repolarization processes of the cardiac muscle. This study allows recording the electrical activity of myocardial cells and the underlying differences in electric potential: the magnitude of this difference is measured in millivolts (mV), and its duration is measured in seconds. The ECG is indicated when an irregular rhythm is detected during physical examination, such as bradycardias, tachycardias or arrhythmias that are not secondary to breathing, in animals with a history of syncope or weakness, for monitoring the effectiveness of antiarrhythmic therapy, in cases of putative pleural or pericardial effusion, and also in systemic diseases that lead to arrhythmia. For a reliable assessment, the ECG must be evaluated in conjunction with findings from the physical examination and clinical signs of each patient.

El electrocardiograma (ECG) es una importante herramienta utilizada en el diagnóstico de arritmias cardiacas, ya que proporciona la representación gráfica de los procesos de despolarización y repolarización del músculo cardiaco, permite el registro de la actividad eléctrica de las células del miocardio y registra las diferencias de los potenciales eléctricos, la magnitud de esta diferencia de potencial eléctrico se mide en milivoltios (mV) y su duración se mide en segundos. El electrocardiograma está indicado cuando un ritmo irregular se detecta durante un examen físico, incluyendo bradicardias, taquicardias o arritmias que no son secundarias a una arritmia respiratoria sinusal; en los animales con una historia de desmayo o debilidad; para el control de la eficiencia de la terapia antiarrítmica; ante la sospecha de derrame pleural o pericárdico, así como en las enfermedades sistémicas que conducen a una arritmia. Para obtener un resultado fiable, el ECG debe ser evaluado conjuntamente con el examen físico y los signos clínicos de cada paciente.

O eletrocardiograma (ECG) é uma importante ferramenta utilizada no diagnóstico de arritmias cardíacas, já que fornece a representação gráfica dos processos de despolarização e repolarização do músculo cardíaco, um estudo que permite registrar a atividade elétrica das células miocárdicas e as diferenças de potenciais elétricos - a amplitude dessas diferenças de potencial elétrico é medida em milivoltes (mV), e sua duração, em segundos. O eletrocardiograma é indicado quando se detectam irregularidades do ritmo durante o exame físico, incluindo bradicardias, taquicardias ou arritmias que não sejam secundárias à respiração em animais com história de síncope ou fraqueza monitoração da eficácia de terapia antiarrítmica suspeita de efusão pleural ou pericárdica e doenças sistêmicas que levam a arritmia. Para uma avaliação fidedigna, o ECG deve ser avaliado em conjunto com o exame físico e os sinais clínicos de cada paciente.
Electrocardiogram in dogs: a review
Electrocardiograma en perros: revisión
Keywords: Cardiology; Electrocardiography; Arrhythmias; Cardiología; Electrocardiografía; Arritmias; Cardiologia; Eletrocardiografia; Arritmias